The impact of accompaniment on the training and competencies of psychology students for clinical practice: a quasi-experimental study - Gallo-Giunzioni, Karla; Kasprzak, Agata; Santiago, Elvira (Frontiers in Psychology, 2026)
IntroductionTraining in psychology requires not only theoretical knowledge but also the development of practical competencies for intervention in healthcare settings. This study aimed to evaluate the effectiveness of a teaching innovation program based on simulated contexts under the accompaniment and supervision of a qualified instructor, designed to strengthen competencies essential for future professional practice.MethodsA program was implemented based on the practical application of intervention and assessment tools in simulated clinical settings. A pre-post design was used with 135 third-year psychology students over two academic years (2023–2024 and 2024–2025), of whom 111 were women (82.2%) and 24 men (17.8%) (N2023−2024 = 68; N2024−2025 = 67) that participated in five simulated clinical sessions. The program's impact was assessed using the COMPES Self-Report Questionnaire, evaluating competencies such as teamwork, autonomous learning, problem-solving, communication, and ethical awareness.ResultsThe results showed significant improvements in all evaluated competencies except for teamwork, possibly due to the limited duration of the program and minimal collaborative interaction among participants.DiscussionExpert supervision and accompaniment appear to be key factors in competence development. This innovative approach reinforces the integration of theory and practice in psychological training and offers a replicable methodology to optimize experiential learning.